Estudios de resistencia a tebufenocida en Spodoptera exigua (Hubner (1808)) - Smagghe, G.=700 1 Medina, P.; Schuyesmans, S.; Tirry, L.; Viñuela, E.
(En, Es)
ilus., 28 ref.
Keywords: SPODOPTERA EXIGUA; CONTROL QUIMICO; INSECTICIDAS; RESISTENCIA A PRODUCTOS QUIMICOS; ESPAÑA